Early REperfusion therapy with intravenous alteplase for recovery of VISION in acute central retinal artery occlusion (REVISION): Study protocol of a phase III trial - Poli, Sven; Grohmann, Carsten; Wenzel, Daniel A.; Poli, Khouloud; Tünnerhoff, Johannes; Nedelmann, Max; Fiehler, Jens; Burghaus, Ina; Lehmann, Monika; Glauch, Monika; Schadwinkel, Hauke M.; Kalmbach, Pia; et al. (International journal of stroke, 2024)
Rationale: Meta-analyses of case series of non-arteritic central retinal artery occlusion (CRAO) indicate beneficial effects of intravenous thrombolysis when initiated early after symptom onset. Randomized data are lacking to address this question. - Aims: The REperfusion therapy with intravenous alteplase for recovery of VISION in acute central retinal artery occlusion (REVISION) investigates intravenous alteplase within 4.5 h of monocular vision loss due to acute CRAO. - Methods: This study is the randomized (1:1), double-blind, placebo-controlled, multicenter adaptive phase III trial. - Study outcomes: Primary outcome is functional recovery to normal or mildly impaired vision in the affected eye defined as best-corrected visual acuity of the Logarithm of the Minimum Angle of Resolution of 0.5 or less at 30 days (intention-to-treat analysis). Secondary efficacy outcomes include modified Rankin Score at 90 days and quality of life. Safety outcomes include symptomatic intracranial hemorrhage, major bleeding (International Society on Thrombosis and Haemostasis definition) and mortality. Exploratory analyses of optical coherence tomography/angiography, ultrasound and magnetic resonance imaging (MRI) biomarkers will be conducted. - Sample size: Using an adaptive design with interim analysis at 120 patients, up to 422 participants (211 per arm) would be needed for 80% power (one-sided alpha = 0.025) to detect a difference of 15%, assuming functional recovery rates of 10% in the placebo arm and 25% in the alteplase arm. - Discussion: By enrolling patients within 4.5 h of CRAO onset, REVISION uses insights from meta-analyses of CRAO case series and randomized thrombolysis trials in acute ischemic stroke. Increased rates of early reperfusion and good neurological outcomes in stroke may translate to CRAO with its similar pathophysiology. - Trial registration: ClinicalTrials.gov: NCT04965038; EU Trial Number: 2023-507388-21-00.